Unified Gas Kinetic Scheme and Direct Simulation Monte Carlo Computations of High-Speed Lid-Driven Microcavity Flows (Communications in Computational Physics, 2018)
Accurate simulations of high-speed rarefied flows present many physicaland computational challenges. Toward this end, the present work extends the UnifiedGas Kinetic Scheme (UGKS) to a wider range of Mach and Knudsen numbers by implementingWENO (Weighted Essentially Non-Oscillatory) interpolation. Then the UGKSis employed to simulate the canonical problem of lid-driven cavity flow at high speeds.Direct Simulation Monte Carlo (DSMC) computations are also performed when appropriatefor comparison. The effect of aspect ratio, Knudsen number and Mach numberon cavity flow physics is examined leading to important insight.